Peripapillary microcirculation in Leber hereditary optic neuropathy. Issue 1 (26th September 2018) - Kousal, Bohdan; Kolarova, Hana; Meliska, Martin; Bydzovsky, Jan; Diblik, Pavel; Kulhanek, Jan; Votruba, Marcela; Honzik, Tomas; Liskova, Petra
Abstract: Purpose: In this prospective observational comparative case series, we aimed to study the peripapillary capillary network with spectral‐domain optical coherence tomography angiography (OCT‐A) in Leber hereditary optic neuropathy (LHON). Methods: Twelve eyes of six individuals, of these three males (five eyes) after clinical onset of visual impairment were imaged by OCT‐A with scans centred on optic discs. Control group consisted of 6 eyes with no visual impairment. Results: The three affected individuals lost vision 6 years (at age 22 years), 2 years and 3 months (at age 26 years) and 1 year and 2 months (at age 30 years) prior to OCT‐A examination. All five affected eyes had alterations in density of the radial peripapillary microvascular network at the level of retinal nerve fibre layer, including an eye of a patient treated with idebenone that underwent almost full recovery (best corrected visual acuity 0.87). Interestingly, the other eye showed normal ocular findings 14 months after onset. Results of OCT‐A examination in this eye were unfortunately inconclusive due to a delineation error. At the level of the ganglion cell layer differences could be also noted, but only in two severely affected individuals. There were no differences between unaffected mutation carriers and control eyes. Conclusion: Optical coherence tomography angiography scans confirmed that the peripapillary microvascular network is highly abnormal in eyes manifesting visual impairment due to LHON. These findings support the hypothesis that microangiopathy contributes to the development of vision loss in this mitochondrial disorder.